War in the feudal zone: state failure and the abandonment of anthropological research in Mexico and Central America. (2nd January 2018) - Yaworsky, William; Wladyka, Dawid
Abstract : We analysed the extent to which violent, organised crime has disrupted anthropological research in Mexico and Central America by conducting a survey of anthropologists who work in the region. We found that although anthropologists will continue research in regions they perceive to have the socio-economic characteristics of a failed state they are far less inclined to work in areas that they perceive as excessively violent. We continue with examination of the state failure and feudalisation that are affecting the region. We conclude that in the feudal zones, the state has lost its comparative advantage in the use of force and that state intrusion into these areas increases armed collective violence in a manner similar to that described in the literature on warfare in tribal zones.